Black bone syndrome in broilers fed ethanolic extract of mango seeds - de Melo, Marcelle C.A. (Poult Sci, 2020)
This study aimed to evaluate the incidence of black bone syndrome (BBS) in broiler chickens fed with ethanolic extract of mango seed (EEMS). A total of 504 one-day-old male broilers were used in a completely randomised design assigned with 7 experimental diets and 6 replicates of 12 broilers per experimental plot. The experimental diets consisted of: diet without addition of synthetic antioxidant; diet with addition of synthetic antioxidant (200 ppm); and 5 levels of EEMS: 200 ppm, 400 ppm, 600 ppm, 800 ppm, and 1,000 ppm. Two methods of cooking (roasted and boiled) were used to prepare thigh samples. According to the results, the diets did not significantly influence the performance of the broilers. BBS incidence was higher in broilers fed a diet without antioxidants and was reduced with EEMS dietary inclusion, with the lowest incidence occurring with the inclusion of 1,000 ppm. The synthetic antioxidant butylated hydroxytoluene in the diet promoted a significantly higher BBS incidence than that obtained with 800 and 1,000 ppm EEMS and did not differ from the other diets. Of the cooking methods, a higher BBS incidence was observed for the boiled method. For the meat coloration and bone parameters, there were no significant interactions between the factors, diets and cooking methods. There was a linear reduction in the darkening score and linear increase in the luminosity (L∗) of the meat with increasing EEMS in the diet. With regard to the cooking method, the boiled thighs had lower luminosity (L∗), higher parameter a∗, and lower parameter b∗ values because of more pronounced meat darkening. The roasted bones were less heavy, dense, and flexible. A negative correlation was observed between the degree of darkening of the meat that characterizes the BBS with the luminosity (L∗) and intensity of yellow. We concluded that the addition of EEMS contributes to a reduced darkening of meat that characterises the BBS and recommend the dietary inclusion of 1,000-ppm EEMS.